Transmisi Data Usb Keylogger Secara Real-Time Melalui Gelombang Elektromagnetik Pada Frekuensi 2.4ghz - Dalimunthe, Muhammad Iqbal Luthfi; Sunarya, Unang (eProceedings of Applied Science, 2024)
A USB keylogger is a device that can record every typing activity on a keyboard, and secure real-time data transmission is the main focus in the development of this tool. In this research, the author designs practical and efficient hardware, and implements encryption technology to protect data from potential intrusion or manipulation by unauthorized parties. This research includes transmission distance testing, hardware design optimization, and performance evaluation under various environmental conditions. The test results show that this tool is able to transmit real-time data stably and safely on the 2.4GHz frequency. By implementing strict security protocols, this tool is expected to be a reliable solution in developing cyber security penetration tools. The conclusion of this research is that the development of a USB Real-time Keylogger with data transmission via the 2.4GHz frequency has succeeded in meeting the stated objectives, namely creating a practical, efficient and safe tool. The author hopes that this report can make a useful contribution to the field of cyber security and become a reference for the development of similar technology in the future. Keywords— USB Keylogger, Real-time Transmission, 2.4GHz, Cyber ​​Security.